Development of bio-reactor for the production of hydrogen from plant biomass - Obazu, Franklin Ochuko (My University, 2013)
The research objectives for this study involved the development of a modified thermophilic fluidized bacterial granular bed bioreactor system for the production of biohydrogen from sucrose. The granules were comprised of an undefined anaerobic thermophilic multispecies consortium of bacteria. In order to establish the thermophilic bacterial granules, the bioreactor was operated as a chemostat under increasing dilution rates. This promoted the selection and enrichment of thermophilic granules comprised of a multispecies bacterial consortium. Endo medium which is one of the most basic bacteriological nutrient mediums was used as the nutrient supply in the granule generating chemostat experiments. Bacterial inoculums from mesophilic environments were used to induce and establish thermophilic and extreme-thermophilic adapted bacterial granules in the chemostat experiments. Granulation was successfully induced under a thermophilic temperatures ranging from 55 oC to 70 oC within a period ranging from 5 to 14 days. Bioreactor design and operation was modified so as to increase both hydrogen yield (HY) and volumetric hydrogen productivity (HP). It was found that in order to increase both HY and HP it was necessary to implement a number of modifications in bioreactor design and operation. The two key operational parameters were temperature and de-gassed effluent recycling rate through the bioreactor bed. Through the incorporation of a solid-liquid separator in the form of 11.6 L settling column, bacteria granular bed wash out was prevented for a 5.0 L thermophilic bioreactor system operated at high volumetric biomass densities, low hydraulic retention times and high degassed effluent recycle rates. Stability of the bioreactor operation in terms of volumetric hydrogen productivity (L H2/L/h), %H2 content and pH maintenance was readily maintained for 50 days. While volumetric hydrogen productivity increased with bacterial biomass density, both hydrogen yield (mol H2/mol glucose) and specific hydrogen productivity (L H2/g/h) declined with increasing biomass density. In this process the rate of physical removal of H2 trapped in the bulk liquid phase surrounding the fluidized granules reduced the thermodynamic constraints preventing the simultaneous achievement of high HPs and high HYs in a granular fluidized bed derived from an undefined bacterial culture. It became evident that a thermophilic temperature alone was an insufficient condition to achieve simultaneously high HPs and high HYs. It also became evident that hydraulic retention time for degassed effluent recycling was a critical for the simultaneous achievement of high HPs and high HY. It was discovered that a reduction in the total volume of bioreactor system relative to increasing rates of degassed effluent recycle was a necessary condition for the simultaneous achievement of both high HPs and high HYs. Thus at thermophilic temperatures any increase in the bioreactor system volume should also be accompanied by a concomitant increase in the rate of degassed effluent recycling so the HRT always remained below the critical threshold necessary for the simultaneous achievement of high HPs and high HYs. Once it was demonstrated that by the adjusting bioreactor system volume and the degassed to effluent recycle rates both high HPs and high HYs could be achieved only under thermophilic conditions it was necessary to show that under these operational condition the system would produce net positive work in terms of hydrogen energy production. It was shown through modeling heat exchanges that if the bioreactor was effectively insulated and waste heat was recycled or recovered then net positive work was accomplished by the bioreactor system. Bacterial granules grown from mesophilic inoculant were adapted to generate H2 from sucrose under a range of thermophilic temperatures (55, 60, 65, 70 oC). Attainments of two H2 generation process goals were assessed. First, whether a net positive net energy balance at thermophilic temperatures and high effluent recycle rates were attainable. Secondly, whether the volumetric hydrogen productivities were sufficient to drive a 5 kW fuel cell when scale-up to 1 m3
Keywords: Plant biomass.; Hydrogen.